The largest reference range study for hematological parameters from Turkey: A case control study - Tekkeşin, Nilgün; Beköz, Hüseyin; Tükenmez, Faruk (My University, 2014)
Objectives: Accurate, reliable laboratory reference ranges are essential for effective clinical evaluation and monitoring. We present robust reference ranges established for hematology parameters using the Sysmex XT2000i analyzer. Methods: Blood samples were taken from 17409 healthy adults (19 to 49 years, 51.4% men and 48.6% women) and routine hematology analysis performed. Patients were assessed as healthy on the basis of a medical history and routine medical examinations. Serum hematinic assays (vitamin B12, folate, iron and ferritin) were also analyzed in order to exclude the potential anemia existence. Results: There was a statistically significant difference (p<0.001) between men and women, with the former showing higher CBC values, except WBC, neutrophil and platelet counts compared to females. Several differences were observed when compared to previously established values from Turkey, most notably in leucocytes and platelets. Our findings for CBC parameters, except leucocyte count and MCV are in general agreement with previously published data from more limited trials undertaken in other countries. Conclusions: In spite of the uncontrolled factors influencing hematological values, this study permitted to establish the new hematological reference values in Turkey, especially living near sea level. In the absence of previously detailed investigated hematological reference values in Turkey, we offered to use these results for clinical management of Turkish patients and interpretations of laboratory data for research purpose.

Amaç: Doğru, güvenilir laboratuvar referans aralıkları etkili klinik değerlendirme ve izleme için gereklidir. Biz hematoloji parametreleri için belirlenmiş mevcut referans aralıklarını Sysmex XT2000i analizörü kullanarak sunuyoruz.Yöntemler: kan örnekleri 17409 sağlıklı erişkinden (yaş aralığı, 19 ile 49 yıl arasında, %51,4 erkek ve %48,6 kadın) alındı ve rutin hematoloji analizi yapıldı. Hastalar, tıbbi geçmişleri ve rutin muayenelerine dayanarak sağlıklı olarak değerlendirildi. Serum hematinik testleri (vitamin B12, folat, demir ve ferritin) de çalışılarak potansiyel anemi varlığı hariç tutuldu. Bulgular: Kadın ve erkek arasında belirgin istatistiksel farklılık (p<0,001) olup erkeklerde kadınlara göre tam kan sayımı parametreleri, beyaz küre hücreleri, nötrofil ve trombositler hariç daha yüksekti. Daha önce Türkiye'den bildirilen değerler ile karşılaştırıldığında başta lökositler ve trombositler olmak üzere birçok farklılıklar tespit edildi. Tam kan sayımı parametreleri bulgularımız, diğer sınırlı sayıda katılımcının yer aldığı ülkelerden elde edilen yayınlanmış verilere göre kıyaslandığında ise lökosit sayısı ve MCV hariç genel bir uyumluluk içindeydi. Sonuçlar: Hematolojik değerleri etkileyen kontrol edilemeyen faktörlerin aksine, bu çalışmada, Türkiye' de özellikle deniz seviyesinde yaşayanlar için yeni hematolojik referans değerlerinin oluşturulmasına izin vermiştir. Türkiye'de daha önce ayrıntılı incelenen hematolojik referans değerleri yokluğundan dolayı, bu sonuçların Türk hastaların klinik açıdan yönetimleri ve araştırma amaçlı laboratuvar verilerinin yorumlanması adına kullanılmasını öneriyoruz.
Türkiye’ den hematolojik parametrelerin en büyük referans aralığı çalışması: Bir vaka-kontrol araştırması
Keywords: Complete Blood Count; Hematology; Reference Range; Tam Kan Sayımı; Hematoloji; Referans Aralığı